Application of Torsional and Longitudinal Elastic Waves in Mechanical Systems - A. Pielorz (Engineering Transactions, 1983)
One-dimensional elastic waves are used of the investigation of mechanical system consisting of an arbitrary number of elastic elements and rigid bodies. These systems may be loaded by non-periodic forces and their elements may collide with each other. Elastic elements have finite lengths and are assumed to deform longitudinally or torsionally. Analytical solutions of the systems are given in the form of recurrence formulae. These enable to determine velocities, strains and displacements in an arbitrary cross-section of elastic elements at an arbitrary time instant, taking into account equivalent damping. As an example, the model of crankshaft of a one-cylinder engine is considered.